The Relationship Between Teaching Methods and Student Engagement in English Classrooms - Fitrah S, Muh. Aidil; Muhayyang, Maemunah; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study focused on analyzing the relationship between the teaching methods employed by teachers and the level of student engagement in the English classroom. The thesis used a quantitative correlational design. The population of this research included 12th-grade students from six classes at SMAN 12 Bulukumba in the 2023/2024 academic year, selected through a random sampling technique. The sample consisted of 28 12th-grade MIPA students from SMAN 12 Bulukumba. The instrument used for this research was a questionnaire. The results demonstrated a significant connection between the instructional techniques utilized by teachers and the degree of student involvement at SMAN 12 Bulukumba. Data processing using SPSS revealed that the teaching methods employed by the teachers were effective, with a mean value of 56.69. In contrast, students' participation was categorized as moderate, with a mean value of 38.76. Additionally, the examination unveiled a correlation between the teaching methodologies adopted by teachers and the level of student engagement, with a significance value (Sig) of 0.000, well below the threshold of 0.05. Therefore, the hypothesis (Ha) was accepted.Keywords: Teachers’ Teaching Methods, Students’ Participation in English   Classroom.